2015
DOI: 10.1103/physreve.92.012202
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation in wet granular matter under vertical vibrations

Abstract: Experiments on a thin layer of cohesive wet granular matter under vertical vibrations reveal kink separated domains that collide with the container at different phases. Due to the strong cohesion arising from the formation of liquid bridges between adjacent particles, the domains move collectively upon vibrations. Depending on the periodicity of this collective motion, the kink fronts may propagate, couple with each other and form rotating spiral patterns in the case of period tripling, or stay as standing wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 42 publications
6
22
0
Order By: Relevance
“…For the dry case, there is a clear tendency of forming surface waves, in agreement with a previous experiment conducted in Q2D [43]. For wet particles under the same driving conditions, surface waves are suppressed, as expected from previous investigations on wet granular materials [36,40]. An increase of L x while keeping the same granular layer thickness and a change to periodic boundary condition in the x direction yield qualitatively the same behavior.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…For the dry case, there is a clear tendency of forming surface waves, in agreement with a previous experiment conducted in Q2D [43]. For wet particles under the same driving conditions, surface waves are suppressed, as expected from previous investigations on wet granular materials [36,40]. An increase of L x while keeping the same granular layer thickness and a change to periodic boundary condition in the x direction yield qualitatively the same behavior.…”
Section: Methodssupporting
confidence: 89%
“…Note that it takes less than 1/10 of a vibration period for the wave to propagate through the granular layer and redistribute the injected energy. According to previous investigations [40,42], the periodicity of both the dry and the wet granular layer under vertical vibrations can be estimated approximately with a single particle colliding completely inelastically with the container. For the driving condition used here (f = 10 Hz, Γ = 4), the granular layer undergoes a period doubling bifurcation and consequently the CM trajectory Other parameters are the same as in Fig.…”
Section: Wave Propagationmentioning
confidence: 93%
See 1 more Smart Citation
“…As Γ increases to ≈ 4.7, some particles start to move and form small clusters (see the reconstructed image at Γ = 6.8). The critical acceleration Γ c can be understood from the force balance F d = F b + G, where the magnitude of the capillary force F b , gravity G and driving force F d can be estimated with |F b | = πσd cos α with contact angle α ≈ 0, |G| = πρ p d 3 g/6, and |F d | = Γ c G respectively [18]. Consequently, we estimate Γ c ≈ 4.5, which agrees well with the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of rigidity leads to an easily moldable material such as wet sand on the beach for sculpturing [7,8]. In the pendular regime [3] with capillary bridges formed between adjacent particles, previous investigations showed that the collective behaviors of partially wet granular materials, such as clustering, phase transitions and pattern formation, are related to the capillary force induced by the wetting liquid [9][10][11][12][13]. However, as more liquid is added, it is still challenging to understand how a wetting liquid film advances inside a geometrically heterogeneous granular packing, as well as how the particles respond to the capillary interactions induced by the additional wetting liquid.…”
Section: Introductionmentioning
confidence: 99%